Kedudukan Hukum Dan Tanggung Jawab Penilai Kerugian Asuransi Di Indonesia - Syalshabilla Andi Puteri; Risma Seli Novitasari; Nandhini Wulandari Nur Safitri (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
The problem that often arises in insurance is the problem of claims. Claims submitted by the insured to the insurer often have differences in perception between each party. This difference in perception is often a problem and difficult for the insured to accept because what is in the mind of the insured if there is a disaster that harms the insured object, the insured can easily file a claim. There are different interpretations and a person's lack of understanding of his rights and obligations in the insurance agreement. Therefore, the role of insurance loss assessors is very necessary to avoid disputes. The results showed that, insurance loss assessors are regulated in Law Number 40 of 2014 concerning Insurance, Government Regulation of the Republic of Indonesia Number 39 of 2008 concerning the Second Amendment to PP Number 73 of 1992 concerning the Implementation of Insurance Business, Decree of the Minister of Finance of the Republic of Indonesia No. 425 / KMK.06 / 2003 concerning Licensing and Implementation of Business Activities of Insurance Business Support Companies, Financial Services Authority Regulation Number 2 / POJK.05 / 2014 concerning Good Corporate Governance for Insurance Companies, Financial Services Authority Regulation Number 70/POJK.05/2016 concerning Business Operation of Insurance Brokerage Companies, Reinsurance Brokerage Companies, and Insurance Loss Appraisal Companies Code of Conduct issued by the Indonesian Insurance Loss Appraisal Association. Then for the role of insurance loss assessors, it has been regulated and supervised by the Indonesian Insurance Loss Appraisal Association (APKAI).